Remington-UMC Exhibit
Note on front: Palace of ManufacturesPanama-Pacific Exposition "A notable showing of modern firearms and ammunition-a revelation alike to sportmen, sporting goods dealers and the layman." Front also depicts small photos of "Arms and Ammunition Factory, Bridgeport, Conn. Ammunition Factory, Windsor, Ont.,Canada Arms Factory Ilion,NY."